THE SOFTWARE PACKAGE FOR DATA STREAM SCRAMBLING - P. A. Kadiev; P. I. Kadiev; T. M. Mirzabekov (Вестник Дагестанского государственного технического университета: Технические науки)
Abstract. It is proposed a software package for multivariate stepwise transformation of the text flow in order to increase resistance to protect against unauthorized access, and a package to restore the converted text. The basis of the proposals: the formation of nxn-array from the elements of a data flow, preliminary transposition of the array elements to form an array, each row and each column of which includes one and one only element from each row and each column of the source array, following reading on the options selected by the user.Package for direct conversion includes: a module for forming an array from the input flow; transposition module of array elements according to the scheme of Latin squares; reading module of rows or columns of the array to one of the following algorithms: sequential reading; reading of rows or columns with even indices and then odd ones;reading the row or column with odd indices, and then the even; reading at random route, which is generated by the program; reading at the route determined by the user.Package for restoring of the original message by the inverse transform comprises: a channel array forming module from the data flow; recovery module from the channel array - the array of Latin square type; the original array module; the original message restoring module.